EFFECT OF HUSBAND'S SUPPORT IN THE IMPLEMENTATION OF OXYTOCIN MASSAGE BY MIDWIFE ON THE PRODUCTION AND TIME OF COLOSTRUM SECRETION AMONG POST C-SECTION DELIVERY WOMEN - Novia Sari; Lucky Herawati; Agus K. Rubaya (Bajang Institute, 2021)
Objective: To determine the effect of husband's support in the implementation of oxytocin massage by midwife on the production and time of colostrum secretion among post C-Section delivery women.Methods: A quasi-experimental study with a post-test only group design at hospital in DIY in April-June 2020. The samples consisted of 32 respondents, 16 post C-Section delivery women with oxytocin massage who received husband's support and 16 respondents with oxytocin massage without husband’s support. The preparation of husband’s support was conducted through training by midwife to the husbands using a booklet for 80 minutes. Data analysis in this study used univariate, Independent t-test, and MANOVA with a significance level of 95%.Results: Evaluation showed that 68.75% of post C-Section delivery women received good husband’s support. The mean colostrum production in the oxytocin massage group by midwife with husband's support was 3.61 cc and the mean time of colostrum secretion was 4.13 hours better than oxytocin massage without husband's support.Conclusion: Husband's support in the implementation of oxytocin massage by midwife had an effect on the production and time of colostrum secretion among post C-Section delivery women with p-value <0.0001.